Translation and Validation Scale for Assessment and Rating of Ataxia in Urdu Language for Cerebral Palsy Patients - Nimra Afzal, Shoaib Waqas, Muhammad Tariq, Asifa Javaid, Hafiz Muhammad Asim (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To translate the Scale for assessment and rating of Ataxia from English to Urdu language Methods: The study employed a linguistic validation study design with a non-random sample approach and was done at different clinical setups of Lahore. Parents of children with ataxic cerebral palsy with children aged 2 to 15 years old who speak Urdu should contact us. Sara’s English version was translated into Urdu by two translators, one with a medical background and the other with a technical background in Urdu, both proficient in Urdu and English. Two individuals with medical and technology backgrounds who are competent in Urdu to English translation reverse translated the translated versions of SARA-Urdu I and SARA-Urdu II into English. The re-translated versions of SARA-Urdu I and SARA-Urdu II were translated back into English (SARA English III and SARA English IV). The translated versions were compared and generated a new Urdu version SARA Urdu-V. The data was entered into the SPSS version 23 application, which was also used to analyze it. Results: The translated version of the SARA scale has a Cronbach’s alpha of 0.883. The inter-item correlation between the total SARA score and the eight domains of gait, stance, sitting, speech disturbance, finger chase, nose finger test, fast alternating hand movements, and heel shin slide was 0.131, 0.046, 0.159, 0.188, 0.136, 0.400, 0.698, and 0.450, respectively, after the translation of the Urdu version of SARA. For test retest reliability, the Pearson correlation value varied from 0.400 to 0.842. Conclusion: The Urdu version of SARA has appropriate internal consistency and fair inter-item correlation, and hence may be utilized by Urdu speakers. Keywords: Cerebral palsy, Cerebellar ataxia, Scale for assessment and rating of Ataxia